Characterization of PVDF Hollow Fiber Membrane for CO2 Stripping by Atomic Force Microscopy Analysis - Rosmawati, Naim; Khulbe, K.C.; A. Fauzi, Ismail; T., Matsuura (Elsevier, 2013)
Microporous polyvinylidene fluoride (PVDF) membranes with various concentrations of lithium chloride additives were prepared for CO2 stripping test. Physical membrane characterizations such as atomic force microscopy analysis, gas permeation, contact angle measurement and liquid entry pressure were also conducted. Correlations among the membrane properties, i.e. contact angle, gas permeation, mean pore size, nodule aggregates and surface roughness obtained from experimental analysis were discussed. The overall trend showed that increasing lithium chloride concentration has decreased the mean pore size, mean nodule aggregates and mean surface roughness of the membrane. On the contrary, the membrane liquid entry pressure has been significantly improved. It was found that the mean pore size determined by tapping mode atomic force microscopy (TM-AFM) is 2.3 to 2.7 times larger than that of obtained from gas permeation test. The decreases in nodule size, mean pore size and low surface roughness have contributed to the enhancement of CO2 stripping performance in membrane contactor system. Increasing LiCl concentration has increased the CO2 stripping flux and membrane mass transfer coefficient. However, the concentration of LiCl showed minimal effect on the liquid side mass transfer coefficient.